2020
DOI: 10.1111/jan.14726
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision‐making in dialysis choice has potential to improve self‐management in people with kidney disease: A qualitative follow‐up study

Abstract: Aims To explore how patients remained involved in their treatment and care of their own health following a shared decision‐making intervention for dialysis choice. Design A follow‐up study using semi‐structured interviews. Methods Individual interviews with 13 patients were conducted immediately following their participation in a shared decision‐making intervention for dialysis choice and again 3 months after initiating dialysis. This study reports findings from the follow‐up interviews 3 month after dialysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…Increasing evidence suggests that discussions on terminal care preferences are delayed or omitted by clinicians [39]. End-of life conversations including those nurse-led discussions, can enhance patient autonomy [40] or engagement in their own health management [41], and that patient subgroups using decision aids are less inclined to request aggressive treatments towards the EOL [42]. To address this gap, our goal was to enable an early and standard conversation ow by a range of clinicians including non-doctors in preparation for the di cult decision time.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that discussions on terminal care preferences are delayed or omitted by clinicians [39]. End-of life conversations including those nurse-led discussions, can enhance patient autonomy [40] or engagement in their own health management [41], and that patient subgroups using decision aids are less inclined to request aggressive treatments towards the EOL [42]. To address this gap, our goal was to enable an early and standard conversation ow by a range of clinicians including non-doctors in preparation for the di cult decision time.…”
Section: Discussionmentioning
confidence: 99%
“…The patients emphasized that the team members should give them more empathy and patience, and be willing to answer any questions that patients may have about the preparation and initiation of renal replacement therapy. These studies [22][23][24][25][39][40][41][42][43] (studies 3,7,8,9,13,14,17,18,32) shed light on how patients can get the exact treatment. First, patients should have relevant knowledge and educational background to their disease.…”
Section: Education Guides Patients To Choose Treatment Methodsmentioning
confidence: 99%
“…Predialysis care and education should be different for older patients, who will delay decision-making until the time of facing obvious uremic symptoms, threatening blood tests or paternalistic guidance from their nephrologist Study 31 [ 46 ] US 14 To explored patients' reasons for choosing conservative management Semistructured interview Thematic analysis High The information that patients reported receiving from clinical staff differed between units. Patients from units with a more established conservative management pathway were more aware of conservative management, less often believed that dialysis would guarantee longevity, and more often discussed the future with staff Study 32 [ 43 ] Denmark 13 To explore how patients remained involved in their treatment and care of their own health following a shared decision-making intervention for dialysis choice Semistructured interview Systematic text condensation High Following the shared decision-making intervention, patients who chose home-based treatment had become more involved in their treatment and care of their own health. The involvement of relatives and support from healthcare professionals contributed positively to this.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in renal care have shown that shared decision‐making interventions involve patients in their decision‐making process (Finderup et al, 2019) and that most patients made an informed decision based on their preferences (Finderup et al, 2020). Furthermore, studies have reported that patients being involved in decision making become more involved in their treatment and health over time (Finderup et al, 2021) and that probably more patients choose a home‐based treatment than a hospital‐based treatment after a shared decision‐ making process (Finderup et al, 2018).…”
Section: Figurementioning
confidence: 99%